Trauma informed practices in education and social justice: towards a critical orientation - Mark Boylan (International Journal of School Social Work, 2021)
Increasingly, educational practitioners committed to social justice embrace trauma-informed practices and those who advocate for and enact trauma-informed practices are committed to social justice. However, connecting social justice to trauma-informed practice requires greater conceptual clarity than is currently found, given the malleable meanings of both 'trauma informed' and 'social justice'. Further, the complex relationship between these educational aims is under-examined. To address these issues, an analytical framework is developed that brings together a model of forms of trauma-informed practice in education with orientations to social justice. This draws on models of social justice developed in social work and teaching, and teacher education. Applying this framework to trauma-informed practice indicates that trauma- informed practice, as so far developed, generally has either a conservative or a socially liberal social justice orientation. Practices are proposed that align with a critical orientation, which attends to cultural and structural relationships implicated in trauma and adversity in childhood. A critical orientation should not only consider practice but also be informed by further theoretical, philosophical and ethical engagement as part of a project of activist professionalism across educational professions.
Keywords: trauma informed; trauma sensitive; social justice; social work; teaching; school mental health; critical